Effect of short-term heat acclimation training on kinetics of lactate removal following maximal exercise - Dileo, T. D.; Powell, J. B.; Kang, H. K.; Roberge, R. J.; Coca, A.; Kim, J. H. (The Journal of Sports Medicine and Physical Fitness, 2016)
ABSTRACT: Aim: Heat acclimation (HA) evokes numerous physiological adaptations, improves heat tolerance and has also been shown to enhance lactate (LA) responses during exercise, similar to that seen with endurance training. The purpose of this study was to examine whether HA improves the body's ability to remove LA during recovery following maximal exercise. Methods: Ten healthy men completed two trials of maximal treadmill exercise (PRE-- and POST--HA) separated by 5 days of HA. Each day of HA consisted of two 45 minute periods of cycling at ~50% VO2max separated by a 15min rest period in an environmental chamber (Tdb 45°C, RH 20%). In PRE--/POST--HA trials, venous blood was collected during 60 minutes of recovery to determine LA concentrations and removal kinetics (A2: amplitude and y2: velocity constant) using bi--exponential curve fitting. Results: Physiological adaptation to heat was significantly developed during HA, as evidenced by end--exercise Tre (DAY1 vs. 5) (38.89±0.56 vs. 38.66±0.44 °C), Tsk (38.07±.51 vs. 37.66±.48 °C),HR (175.0±9.9 vs. 165.0±18.5 beats/min), and sweat rate (1.24 ±.26 vs. 1.47 ±.27 mmol/L) (p<.05). However, there was no significant difference in either LA concentrations (LA0min: 8.78±1.08 vs. 8.69±1.23; LApeak: 10.97±1.77 vs. 10.95±1.46; and La60min; 2.88±.82 vs. 2.96±.93 mmol/L) or removal kinetics (A2: --13.05±7.05 vs 15.59±7.90 mmol/L and y2: .02±.01 vs .03±.01/min). Conclusion: The present study concluded that, while effective in inducing thermo-physiological adaptations to heat stress, short--term HA does not improve the body's ability to remove LA following maximal exercise. Therefore, athletes and workers seeking faster LA recovery from intense physical activity may not benefit from short--term HA.